2014
DOI: 10.1038/ejcn.2014.80
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vitamin D status during pregnancy: the Mediterranean reality

Abstract: Vitamin D status during pregnancy is linked to bone mineralization of developing fetus, which justifies targeting sufficient levels of vitamin D in pregnant women. Despite high level of sunshine in the Mediterranean regions, maternal hypovitaminosis D remain common in these countries. The aim of this narrative review was to provide potential explanations for this phenomenon in an effort to guide future public health policies and vitamin D intakes during pregnancy. We searched Medline for publications regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 45 publications
(71 reference statements)
1
50
0
3
Order By: Relevance
“…It may be speculated, therefore, that further increases in the levels of vitamin D might translate into a more efficient calcium transfer at the intestine. The point is of interest, because the prevalence of vitamin D insufficiency, including the population of pregnant women, is elevated (8), even in low-latitude countries, where sun exposure is high (9). In this context, it may be conceived that a potential role exists for vitamin D analogs, as these compounds are designed to increase the effects of vitamin D while minimizing pathological hypercalcemia (10).…”
Section: Vitamin Dmentioning
confidence: 99%
“…It may be speculated, therefore, that further increases in the levels of vitamin D might translate into a more efficient calcium transfer at the intestine. The point is of interest, because the prevalence of vitamin D insufficiency, including the population of pregnant women, is elevated (8), even in low-latitude countries, where sun exposure is high (9). In this context, it may be conceived that a potential role exists for vitamin D analogs, as these compounds are designed to increase the effects of vitamin D while minimizing pathological hypercalcemia (10).…”
Section: Vitamin Dmentioning
confidence: 99%
“…The 25(OH)D is metabolized in the kidneys by the enzyme 25-hydroxyvitaminD-1a-hydroxylase (CYP27B1) to active form 1,25-dihydroxyvitamin D [1] this product is tightly regulated by plasma levels parathyroid hormone, calcium and phosphorus levels [6]. Vitamin D concentration >30.0 ng/ml (>75,0 nmol/L considered to be sufficient, insufficient level is between 20 and 30ng/mL (50-75nmol/L) and deficient if it is <20ng/mL (<50nmol/L) [7][8].There are many factors influence Vitamin D levels in the body such as geographical zones, dietary patterns, physical environment, seasons, dark skin pigmentation and obesity [9][10].…”
mentioning
confidence: 99%
“…Observational studies have shown consistent associations between obstetrical clinical outcomes and poor maternal vitamin D status, including preeclampsia, gestational diabetes, low birth weight, increased cesarean section rate, neonatal asthma, seizures, and preterm labor [73][74][75].…”
Section: Vitamin D and Pregnancymentioning
confidence: 97%